EVOLUCIÓN DE LAS POLÍTICAS ACTIVAS DE EMPLEO PARA INMIGRANTES EN ESPAÑA (Revista de História Regional, 2007)
The fundamental objective in this article is to approach the reader to the present reality of the active policies of use on immigrants who are present in the legal ordering of Spain through the subscribed bilateral agreements between both countries. For it, and before beginning the analysis as so of the study object I understand that he is advisable to locate to the reader with general lines introductory on the state of the question and to later connect it with historical antecedents that to the present time consider the relation between the Spanish economic situation from 1975 and the circumstances of the population immigrant worker in Spain. As starting idea is essential to shape the principle by which the right of the people to justice and the personal well-being, directly bound to a work or worthy occupation, happens through the search of these values in places different from the one from birth.